The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1363460718797258
|View full text |Cite
|
Sign up to set email alerts
|

Queer necropolitics of forced migration: Cyclical violence in the African context

Abstract: This article seeks to theorize queer necropolitics—the ability for states to decide who lives and who dies—within the context of forced displacement. In doing so, I link the literature on African sexualities, necropolitics, and queer migration and ask the following questions: How do African states engage in necropolitics that fuel forced displacement for queer people? And, how do forcibly displaced queer migrants navigate and survive in heteronormative spaces within the wider context of racialization in Cape T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Studies used varying gender terms, with eight studies adopting umbrella terms such as ‘queer’ [ 48 , 49 , 50 ], ‘diverse SOGIESC’ [ 51 , 52 ], or a form of ‘LGBTQ’ [ 47 , 53 , 54 ]. Others provided a breakdown of numbers of participants within gender categories according to either self-identification or categories provided by the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies used varying gender terms, with eight studies adopting umbrella terms such as ‘queer’ [ 48 , 49 , 50 ], ‘diverse SOGIESC’ [ 51 , 52 ], or a form of ‘LGBTQ’ [ 47 , 53 , 54 ]. Others provided a breakdown of numbers of participants within gender categories according to either self-identification or categories provided by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Research examining migration pathways for forced migrants in general has demonstrated vulnerabilities to abuse, and risk of physical and sexual abuse along transit routes [ 72 , 73 , 74 ]. Literature has also described victimisation experiences among SOGIE individuals before they migrate, particularly in countries with especially discriminatory gender norms, such as Uganda with severe homophobic and transphobic attitudes [ 2 , 33 , 49 , 50 , 55 , 60 , 61 , 75 , 76 ]. The findings related to this theme underscore the process and pervasiveness of discriminatory behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…This framing of queer necropolitics of forced migration presupposes that host states are engaged in politics of homonationalism. This is not the monopoly of states of the Global North, as Ali H. Bhagat's showed through his work on queer necropolitics of forced migration in South Africa: because of its progressive constitution, the country attracts gay Africans who are then subjected to state-sponsored racist and heterosexist (urban) politics (Bhagat, 2018(Bhagat, , 2020; see also Camminga, 2019). But most countries to which gay migrants are displaced are actually less ambiguous about their rejection of gay migrants.…”
Section: Queer Necropoliticsmentioning
confidence: 99%
“…Embora as causas para os deslocamentos de "LGBTI" sejam múltiplas, é muito frequente que tenham relação com a violência de Estado ou com aquela perpetrada por familiares. Dessa forma, as redes de parentesco que convencionalmente atuam em projetos migratórios deixam de operar quando os familiares são os principais agressores (Andrade, 2019;Bhagat, 2020).…”
Section: Introductionunclassified